The Effectiveness of Learning Action Cell Sessions in Naguilian Central School (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2019)
This study aimed to assess the effectiveness of Learning Action Cell sessions in Naguilian Central School. Specifically, it determined the following: 1. profile of the respondents along with a. educational attainment, b. training and seminars attended over the last three years, and c. performance rating for the last three years 2. extent of implementation of the LACs in terms of; a. pre-implementation, b. implementation, and c. post-implementation 3. level of effectiveness of the LACs in terms of a. professional development along with instruction, ICT integration, assessment and curriculum b. personal development along with human relationships, management, productivity and work ethics 4. the extent of administrative support 5. capabilities and constraints 6. best practices. The researcher employed the descriptive-evaluative research design. Data were collected and analyzed using frequencies and percentages. Respondents were thirty-one teachers, one school head and ninety learners from grade 1-6 of NCS. Survey questionnaires were answered by the respondents while an unstructured interview was conducted to learners to support the responses of the respondents. Findings showed that 1.) the profile of teachers was diverse 2.) there was a “Full Implementation” of LAC’s as perceived by the respondents 3.) level of effectiveness was perceived to be “Highly Effective” 4.) level of administrative support was perceived “Highly Supported” 5.) there were noted capabilities and constraints; constraints were used to formulate LAC’s enhancement program 6.) best practices were determined through Focus Group Discussion and need to be continued or improved. To improve the program,a validated LACs Enhancement Program was developed. The LAC as a K to 12 basic education prog. school-based continuing professional development strategy for the improvement of teaching and learning implies that every teacher should be properly guided and equipped with the know-how of teaching and learning process through revisiting and reviewing some areas or concerned in performing the duties and responsibilities of an effective and efficient teacher. The formulation of this LACs enhancement program was based on the features of the K to 12 Basic Education Prog. as articulated in RA No.10533, the Enhanced Basic Education Act of 2013 and various policies of the DepEd. The indicators that were rated lowest as constraints were considered in the enhancement program.
Keywords: enhancement program, implementation, effectiveness, administrative support